The Fibrotic Role of Phosphatidylinositol-3-kinase/Akt Pathway in Injured Skeletal Muscle after Acute Contusion - Li, H.-Y.; Zhang, Q.-G.; Chen, J.-W.; Chen, S.-Q.; Chen, S.-Y. (International Journal of Sports Medicine, 2013)
Transforming growth factor β (TGF-β) is a multifunctional cytokine with fibrogenic properties. Previous studies demonstrated that Phosphatidylinositol 3-Kinase (PI3K)/Akt/ mammalian target of Ramycin (mTOR), a non-Smad TGF-β pathway, plays an important role in the fibrotic pathogenesis of different organs such as the lung, kidney, skin and liver. However, the role of PI3k-Akt pathway in fibrosis in injured skeletal muscle is still unclear. In this study, we determined the fibrotic role of PI3K-Akt pathway in injured skeletal muscle. We established a mouse model for acute muscle contusion. Western blotting analysis showed that TGF-β, phosphorylated Akt and phosphorylated mTOR were increased in muscles after acute contusion, which indicated that the PI3K-Akt- mTOR pathway was activated in skeletal muscle after acute contusion. The pathway was inhibited by a PI3K inhibitor, LY294002. Moreover, the expression of fibrosis markers vimentin, α SMA and collagen I and the area of scar decreased in injured skeletal muscle after PI3K pathway was blocked. The muscle function improved in terms of both fast-twitch and tetanic strength after PI3K/Akt pathway was inhibited in injured skeletal muscle. In conclusion, activation of PI3K-Akt-mTOR pathway might promote collagen production and scar formation in the acute contused skeletal muscle. Blocking of PI3K-Akt-mTOR pathway could improve the function of injured skeletal muscle.
Keywords: Fibrosis; muscle injuries; phosphatidylinositol-3-kinase; akt; mammalian target of Ramycin